2021
DOI: 10.1371/journal.pone.0246405
|View full text |Cite
|
Sign up to set email alerts
|

“People play it down and tell me it can’t kill people, but I know people are dying each day”. Children’s health literacy relating to a global pandemic (COVID-19); an international cross sectional study

Abstract: The aim of this study was to examine aspects of children’s health literacy; the information sources they were accessing, their information preferences, their perceived understanding of and their reported information needs in relation to COVID-19. An online survey for children aged 7–12 years of age and parent/caregivers from the UK, Sweden, Brazil, Spain, Canada and Australia was conducted between 6th of April and the 1st of June 2020. The surveys included demographic questions and both closed and open questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 23 publications
(26 reference statements)
3
84
0
1
Order By: Relevance
“…Thus, the prevalence of anxiety in Swedish adolescents was 14.7% for NRS>6, and of 5.7% comparing these studies using a cut-off for NRS of NRS>7, compared to 21.8% for Brazilian children [21] . However, there were differences between these data samples, as the Brazilian children were younger than the Swedish adolescents [21] and Brazilian schools had closed, whereas in Sweden schools were still open [36] .…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the prevalence of anxiety in Swedish adolescents was 14.7% for NRS>6, and of 5.7% comparing these studies using a cut-off for NRS of NRS>7, compared to 21.8% for Brazilian children [21] . However, there were differences between these data samples, as the Brazilian children were younger than the Swedish adolescents [21] and Brazilian schools had closed, whereas in Sweden schools were still open [36] .…”
Section: Discussionmentioning
confidence: 88%
“…As part of a larger mixed-methods online survey study, whose findings are reported elsewhere (Bray et al, 2021), we invited children to draw, label and share a picture via Survey Monkey in response to the question 'Why are we all trying to stay at home during the coronavirus?' As children in one country (Sweden) continued to attend school throughout the pandemic, this question was altered slightly to read 'Can you draw a drawing that explains how we should act during the coronavirus epidemic?…”
Section: Methodsmentioning
confidence: 99%
“…These issues have been evidenced more recently in relation to COVID-19 and there has been a call for clearer public health campaigns and messaging (Okan et al, 2020) to enhance health literacy about COVID-19. In many countries, children have been reliant on their parents for information and knowledge about COVID-19 and have shown information gaps that need to be filled about the pandemic (Bray et al, 2021); children have also been excluded from key health messaging efforts in some countries (Rowland and Cook, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted the relevance of parents’ educational styles to communicating health information. Studies have shown that young people depend on their parents to access health information and resources, and, therefore, different approaches are used to share or filter health information [ 11 , 51 ]. As stated above, school influence was also extensively affirmed.…”
Section: Introductionmentioning
confidence: 99%